Growing Ethical Networks : The Fair Trade Market for Raw and Processed Agricultural Products (in Five Parts) with Associated Case Studies on Africa and Latin America - Farnworth, Cathy (Washington, DC: World Bank, 2012)
In the last decade, the "fair trade" of agricultural products and food has emerged as an important tool for creating markets for poor and small-scale farmers and simultaneously promoting pro-poor development. At its most basic, fair trade supports two processes: (1) explicit on-the-ground development for some of the most marginalized and poor actors in international agricultural commodity chains' smallholder farmers and plantation workers; and (2) clearly presenting and making visible the relations sustaining international commodities to consumers. In short, fair trade works to connect Southern producers with Northern consumers through international trade networks dedicated to community development.